As novas formas de racismo e os valores sociais - Rivera, Giovani Amado (2009)
In modern societies, explicit acts of racial and ethnic discrimination are publicly condemned and prohibited by law. Racial prejudice can be compared to an iceberg whose visible part is the clear manifestations and submerged part corresponds to the prejudices not expressed, which is invisibly present in the subjects heads (Carone & Benedict, 2002). The classical psychological theories study prejudice as an universal attitude that exists naturally in individuals or groups and is expressed through derogatory feelings and behaviors. Recent theories (Billig, 1985; Wetherell, 1996; Camino & Ismael, 2004) place these psychological concepts in actual conflicts of social exclusion/inclusion. Accordingly, prejudice turns into the subjective aspect of real conflicts of power between groups and takes place mainly inside dominant groups and may be defined as an "intergroup form of relationship where, in the specific context of asymmetric power relations, derogatory attitudes and hostile and discriminatory behaviors are developed within the dominant groups against members of minority groups for being members of such groups "(Camino & Pereira, 1999). So racism is not a universal phenomenon, but a form of social consciousness that is developed in specific historical situations. Researches show that the respondents from Paraíba seem to have clear awareness of the racial discrimination that is happening in Brazil, but do not accept to take responsibility for this situation (Camino, Silva, Pereira & Machado, 2001; Camino, Silva & Machado, 2004). It was also observed that people praised black people more than white people, but think that Brazilians would do the opposite. This research involved 206 students from public and private universities, with ages ranging from 17 to 49 years, the majority of females (81%), where 52% identified themselves as white skinned, 44.3% of brown skin and 3 , 5% of black skin. Participants responded to the Value Systems Questionnaire as well as the Rejection to Intimacy scale, Perceived distances between different groups of color scale, Symbolic Racism scale and Belief in a Just World scale. Participants responded that 55.2% of Brazilians, 43.2% of students (the respondents themselves) and 60% of the same racial group indicated the system of economic values (profits, wealth and status) as being more important for the white population. As for the questionnaire on the thinking of the black population, 29% of Brazilians, 47% of the students (the respondents themselves) and 56% of black people replied that the social justice (equality, freedom, brotherhood) is the most important. The results show that there is a differentiation between the two populations according to the values that identify themselves, by themselves as by the Brazilians and the participants themselves, indicating a tendency of discrimination through a hierarchy of social values